GSTCD and INTS12 regulation and expression in the human lung - Obeidat, Ma’en; Miller, Suzanne; Probert, Kelly; Billington, Charlotte K.; Henry, Amanda P.; Hodge, Emily; Nelson, Carl P.; Stewart, Ceri E.; Swan, Caroline; Wain, Louise V.; Soler Artigas, María; Melén, Erik; et al. (Public Library of Science, 2013)
Genome-Wide Association Study (GWAS) meta-analyses have identified a strong association signal for lung function, which maps to a region on 4q24 containing two oppositely transcribed genes: glutathione S-transferase, C-terminal domain containing (GSTCD) and integrator complex subunit 12 (INTS12). Both genes were found to be expressed in a range of human airway cell types. The promoter regions and transcription start sites were determined in mRNA from human lung and a novel splice variant was identified for each gene. We obtained the following evidence for GSTCD and INTS12 co-regulation and expression: (i) correlated mRNA expression was observed both via Q-PCR and in a lung expression quantitative trait loci (eQTL) study, (ii) induction of both GSTCD and INTS12 mRNA expression in human airway smooth muscle cells was seen in response to TGFβ1, (iii) a lung eQTL study revealed that both GSTCD and INTS12 mRNA levels positively correlate with percent predicted FEV1, and (iv) FEV1 GWAS associated SNPs in 4q24 were found to act as an eQTL for INTS12 in a number of tissues. In fixed sections of human lung tissue, GSTCD protein expression was ubiquitous, whereas INTS12 expression was predominantly in epithelial cells and pneumocytes. During human fetal lung development, GSTCD protein expression was observed to be highest at the earlier pseudoglandular stage (10-12 weeks) compared with the later canalicular stage (17-19 weeks), whereas INTS12 expression levels did not alter throughout these stages. Knowledge of the transcriptional and translational regulation and expression of GSTCD and INTS12 provides important insights into the potential role of these genes in determining lung function. Future work is warranted to fully define the functions of INTS12 and GSTCD.